The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/w12020325
|View full text |Cite
|
Sign up to set email alerts
|

Syrian Refugees, Water Scarcity, and Dynamic Policies: How Do the New Refugee Discourses Impact Water Governance Debates in Lebanon and Jordan?

Abstract: Since the Syrian crisis and the so-called “Arab Spring”, new discourses have been created, sparking the discursive water governance debates around water scarcity and hydropolitics. In Lebanon and Jordan—where most water resources are transboundary, and where most Syrian refugees have flown in—new discourses of climate change and especially of Syrian refugees as exacerbating water scarcity are emerging, shaping water governance debates. The aim of this paper is to engage in comparative discourse analysis about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…In Lebanon, Hussein found that the water discourse and crisis in Lebanon is often addressed as a national security issue, and that the issue of water scarcity in the country is strongly related to transboundary water control and governance. In addition that the Syrian Refugee in Lebanon created tensions due to blaming the refugees as the cause of water scarcity, unemployment and instability in Lebanon [31]. Zeitoun found that water in the Middle East provides a powerful new perspective on the Palestinian-Israeli water conflict.…”
Section: Introductionmentioning
confidence: 99%
“…In Lebanon, Hussein found that the water discourse and crisis in Lebanon is often addressed as a national security issue, and that the issue of water scarcity in the country is strongly related to transboundary water control and governance. In addition that the Syrian Refugee in Lebanon created tensions due to blaming the refugees as the cause of water scarcity, unemployment and instability in Lebanon [31]. Zeitoun found that water in the Middle East provides a powerful new perspective on the Palestinian-Israeli water conflict.…”
Section: Introductionmentioning
confidence: 99%
“…The complexities of catering for the WASH needs of approximately the 1.5 million Syrian refugees in Lebanon triggered attempts for policy shifts toward more durable solutions for refugees and hosting communities (GoL & UN 2017). It is estimated that 61% of the 272,000 Syrian refugees residing in informal settlements still rely on trucked water that is unregulated and often comes from illegal sources, while the rest of the needs are met from unsafe wells or by illegally tapping into the existing water supply network (Hussein et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Krakow [9] explored international law regarding the human right to water as it impacts people who are stateless, displaced and/or residents of armed conflict zones in the contemporary Middle East. Hussein et al [10] analysed how narratives of water crises and refugees in Lebanon and Jordan are influencing water governance debates.…”
mentioning
confidence: 99%